Altered expression of fibroblast growth factor receptor 2 isoform IIIc: relevance to endometrioid adenocarcinoma carcinogenesis and histological differentiation - Peng, Wei-Xia (e-Century Publishing Corporation, 2014)
Fibroblast growth factor receptor 2 (FGFR2) is activated in many cancers and considered as a potential therapeutic molecular target including for endometrial endometrioid carcinoma (EEC). Overexpression of FGFR2 isoform IIIc (FGFR2IIIc) has been shown to be associated with carcinogenesis in various cancers, but its expression in EEC has not been reported yet to the best of our knowledge. In this study, we identified roles for FGFR2IIIc in EEC carcinogenesis and demonstrated its diagnostic and prognostic values in EEC. FGFR2IIIc expression was compared between 10 normal endometrium, 10 atypical endometrial hyperplasias, and 47 EEC specimens using immunohistochemistry and quantitative real-time PCR. Atypical hyperplasia, Grade 1 (G1), and Grade 2 (G2) differentiated EEC tissues showed significantly higher FGFR2IIIc expression than normal endometrium tissue. However, as compared to G1 and G2 EECs, Grade 3 (G3) differentiated EEC tissue showed lower FGFR2IIIc expression (P<0.05). There was no significant association between FGFR2IIIc expression and patient age, lymph node metastasis, and EEC stage. These results suggest that altered FGFR2IIIc expression plays an important role in EEC carcinogenesis and may occur in precancerous tissues. However, FGFR2IIIc appears to be not related to EEC progression. Some G3 EECs may develop through different carcinogenic processes than G1 and G2 EECs.